2023
DOI: 10.1038/s41368-022-00212-1
|View full text |Cite
|
Sign up to set email alerts
|

Systemic antibiotics increase microbiota pathogenicity and oral bone loss

Abstract: Periodontitis is the most widespread oral disease and is closely related to the oral microbiota. The oral microbiota is adversely affected by some pharmacologic treatments. Systemic antibiotics are widely used for infectious diseases but can lead to gut dysbiosis, causing negative effects on the human body. Whether systemic antibiotic-induced gut dysbiosis can affect the oral microbiota or even periodontitis has not yet been addressed. In this research, mice were exposed to drinking water containing a cocktail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 51 publications
1
13
1
Order By: Relevance
“…Dysbiosis of the gut flora not only damages the intestinal barrier, but also disrupts the oral microbiota and exacerbates bone resorption in periodontitis through Th17/Treg imbalance. Yuan et al found that long-term antibiotic use led to gut ecological dysbiosis, which increased periodontitis-associated pathogens in the oral cavity and decreased oral microbiota probiotics associated with periodontal health, while Th17 cellassociated pro-inflammatory cytokine (IL-17A, IL-6) expression was upregulated and Treg cell-associated cytokine (Foxp3 and IL-10) expression was decreased in periodontal tissues; in contrast, the use of fecal microbiota transplantation (FMT) not only restored the intestinal microbiota of the mice, but even reversed the Th17/Treg imbalance in periodontal tissue and alleviated periodontitis (Yuan et al, 2023). Katarzyna et al found elevated levels of IL-1b, IL-6 and TNF by measuring salivary inflammatory markers in patients with IBD, with elevated levels of TNF-a and IL-6 being strongly associated with the development of periodontitis (Szczeklik et al, 2012); in the Figueredo team's study, inflammation scores in gingival tissue were significantly higher in patients with active IBD (including four cytokines, IL-1b, IL-6, IL-21 and sCD40L) (Figueredo et al, 2017); nevertheless, anti-inflammatory factors such as IL-4 decrease with increasing levels of inflammation, and IL-4 levels were found to be significantly lower in the gingival sulcus of IBD patients with periodontitis (de Mello-Neto et al, 2021).…”
Section: Immune Mechanism Associations Of Periodontitis and Ibdmentioning
confidence: 99%
“…Dysbiosis of the gut flora not only damages the intestinal barrier, but also disrupts the oral microbiota and exacerbates bone resorption in periodontitis through Th17/Treg imbalance. Yuan et al found that long-term antibiotic use led to gut ecological dysbiosis, which increased periodontitis-associated pathogens in the oral cavity and decreased oral microbiota probiotics associated with periodontal health, while Th17 cellassociated pro-inflammatory cytokine (IL-17A, IL-6) expression was upregulated and Treg cell-associated cytokine (Foxp3 and IL-10) expression was decreased in periodontal tissues; in contrast, the use of fecal microbiota transplantation (FMT) not only restored the intestinal microbiota of the mice, but even reversed the Th17/Treg imbalance in periodontal tissue and alleviated periodontitis (Yuan et al, 2023). Katarzyna et al found elevated levels of IL-1b, IL-6 and TNF by measuring salivary inflammatory markers in patients with IBD, with elevated levels of TNF-a and IL-6 being strongly associated with the development of periodontitis (Szczeklik et al, 2012); in the Figueredo team's study, inflammation scores in gingival tissue were significantly higher in patients with active IBD (including four cytokines, IL-1b, IL-6, IL-21 and sCD40L) (Figueredo et al, 2017); nevertheless, anti-inflammatory factors such as IL-4 decrease with increasing levels of inflammation, and IL-4 levels were found to be significantly lower in the gingival sulcus of IBD patients with periodontitis (de Mello-Neto et al, 2021).…”
Section: Immune Mechanism Associations Of Periodontitis and Ibdmentioning
confidence: 99%
“…The gut microbiota may serve as a bridge linking periodontitis and systemic diseases 16 . Recent studies have reported that gut dysbiosis not only exacerbates periodontitis but also increases the incidence and severity of DM 5,17–20 . Periodontitis‐related bacteria can translocate into the gut through the “oral−gut” axis, which can aggravate pre‐existing gut dysbiosis, resulting in more severe periodontitis in turn 5,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that gut dysbiosis not only exacerbates periodontitis but also increases the incidence and severity of DM 5,17–20 . Periodontitis‐related bacteria can translocate into the gut through the “oral−gut” axis, which can aggravate pre‐existing gut dysbiosis, resulting in more severe periodontitis in turn 5,17 . The initiation and progression of prediabetes and DM is related to gut dysbiosis 18,19 .…”
Section: Introductionmentioning
confidence: 99%
“…Such infectious diseases affect over 2.3 billion people worldwide, particularly those who are impoverished or have compromised health. [6][7][8][9] The existing treatment methods are inadequate for vulnerable populations, particularly in severe cases where cariogenic biofilms develop quickly owing to sugary diets and poor oral hygiene, leading to caries that are difficult to manage. [6,10] The antimicrobial treatments currently available are limited to broad-spectrum agents that lack efficacy and specificity against cariogenic biofilms and are minimally effective against dental caries.…”
Section: Introductionmentioning
confidence: 99%